Tinjauan Yuridis terhadap Penerapan Pasal-Pasal KUHP dalam Cybercrime: Studi Kasus Unauthorized Transfer Payment - Juwita, Juwita; Suriyanto, Suriyanto (Neolectura, 2025)
This study examines the application of the provisions of the Indonesian Penal Code (KUHP) in cybercrime, specifically focusing on the case of unauthorized transfer payment. With the rapid development of technology, traditional criminal law faces significant challenges in addressing cybercrime effectively. This research identifies the gaps in existing regulations and highlights the need for more adaptive and comprehensive legal frameworks to combat cybercrime. The study also discusses the role of the Information and Electronic Transactions Law (UU ITE) in dealing with cyber offenses in Indonesia.The research employs a qualitative method with a normative legal approach, relying on primary and secondary legal materials for data collection. The analysis is based on a detailed literature review, including legal documents, court decisions, and previous research. The results show that current provisions in the Penal Code, such as Article 362 and Article 378, are inadequate for addressing the unique aspects of cybercrime, as they do not fully encompass the technological and non-physical nature of such crimes. The UU ITE, though more relevant, still faces challenges in enforcement, particularly in terms of coordination between law enforcement agencies. Moreover, the study emphasizes the need for continuous legal updates to address evolving technological developments and the increasing complexity of cybercrimes. The research concludes that strengthening the enforcement capacity of law enforcement agencies and enhancing international cooperation is essential to effectively combat cybercrime.